Solusi Persamaan Dirac untuk Fermion dengan Model Potensial Penghalang Medan Elektromagnetik - Arista Romadani; Erika Rani (Lambung Mangkurat University Press, 2020)
The solution of the Dirac equation in the presence of the electromagnetic field on the one-dimensional barrier potential is studied. The energy spectrum and the eigenfunction of the Dirac equation obtained by solving the Dirac equation and we introduced annihilation and creation operators for the Hamiltonian has an identical form in the harmonic oscillator. Regions I and III separated by a potential barrier characterized by the gap energy with the eigenfunctions as a sinusoidal function, and region II has the form of an exponent function. We found the eigenfunction involved positive and negative energy moves exponentially when passed through a barrier.